PENGARUH METODE LATIHAN DAN KEMAMPUAN MOTORIK TERHADAP HASIL BELAJAR KETERAMPILAN BOLABASKET - Dwi Purtanto, - (2019)
Tujuan penelitian ini hendak mengkaji mengenai pengaruh metode latihan dikaitkan dengan tingkat kemampuan motorik terhadap hasil keterampilan dasar bola basket. Metode yang digunakan dalam penelitian ini adalah eksperimen dengan desain faktorial 2 x 2. Instrument penelitian yang digunakan adalah (AAHPERD Basketball Test) dan Tes kemampuan motorik. Berdasarkan hasil penghitungan data bahwa metode latihan blok pada tingkat motorik rendah (49.50) > dari kelompok tingkat motorik tinggi (48.38), metode latihan acak pada tingkat motorik tinggi (54.79) > dari tingkat motor ability rendah (47.43). Berdasarkan perolehan perhitungan ANOVA interaksi antara metode latihan dan kemampuan motorik di peroleh nilai signifikansi sebesar 8.95 > 4.00.; The purpose of this study is to examine the effect of training methods associated with the level of motor skills on the results of basic basketball skills. The method used in this study was an experiment with a 2 x 2 factorial design. The study population was students of SMAN 1 Cililin who participated in basketball extracurricular activities. The number of samples was 64 students and the time of the study was 4 weeks, the number of exercises was 12 meetings, with a frequency of 1 week 3 times. The research instrument used was AAHPERD Basketball Test and Motor Ability Test for Menenga School. Based on the calculation of the data that the average result of the block training method at the low motor ability level (49.50)> of the high ability motor group group (48.38), the average random training method at the motor level is high (54.79)> of the motor ability level low (47.43). Based on the acquisition of ANOVA calculations the interaction between the training method and the motor ability was obtained a significance value of 8.95> 4.00. The results of the study are (1) Overall the random method has a better effect than the block training method in improving basic basketball skills for high school students (2) Random training methods have a better effect than the block method in improving skills. basketball on high school students with high motor skills. (3) Block training method provides a better difference in effect compared to the random training method in improving basketball skills with low motor abilities. (4) There is an interaction between the effect of the training method and the motor ability.